Door-to-oral time and in-hospital outcomes in older adults with aspiration pneumonia undergoing dysphagia rehabilitation. Issue 10 (October 2022) - Katayama, Kohta; Kurita, Noriaki; Takada, Toshihiko; Miyashita, Jun; Azuma, Teruhisa; Fukuhara, Shunichi; Takeshima, Taro
Summary: Background & aims: Aspiration pneumonia (AP) is a public health concern among older adults. Previous studies have reported the association between oral intake initiation within 48 h after hospital admission and better in-hospital outcomes among patients with AP. We investigated the association between initiation of oral intake within 24 h and in-hospital outcomes of older patients with AP undergoing dysphagia rehabilitation. Methods: This retrospective cohort study was conducted from April 2015 to September 2020. Door-to-oral time (D2O) was defined as the time from hospital arrival to the first oral intake and was divided into early (within 24 h), middle (between 24 and 48 h), and late (over 48 h). We examined the associations between D2O and in-hospital outcomes: discharge with oral intake (by logistic regression analysis), length of stay, and days from the first oral intake to discharge (by fitting the general linear models with robust variance estimation). Results: Among the 398 patients with AP, 142 (35.7%) were classified into early, 111 (27.9%) into middle, and 145 (36.4%) into late groups. Compared with the late group, we found insufficient evidence that early D2O was associated with a greater likelihood of discharge with oral intake (adjusted odds ratio = 1.09; 95% confidence interval [95% CI]: 0.50 to 2.38). The early group was associated with a shorter length of stay (adjusted length difference [aLD] = −7.14 days; 95% CI: −10.80 to −3.42) but not with shorter days from first oral intake to discharge (aLD = −3.34 days; 95% CI: −6.91 to 0.24). Conclusions: While D2O within 24 h among patients with AP was not associated with a decreased likelihood of discharge with oral intake, it was associated with a shorter length of stay. To improve outcomes without compromising the quality of AP care, early oral intake should be decided based on careful swallowing function assessment.